Investigation Of The X - Ray Shielding Properties Of Concrete Containing Lime Kiln Dust - Ampadu, E.K. (University of Ghana, 2013)
An x-ray dose above the maximum permissible limit is harmful to human beings. A study of x-ray attenuation by materials is an important subject in protecting humans from harmful effects of radiation. Thus it is desirable to have knowledge about materials for effective x-ray shielding. Concrete is the most widely used construction material for this purpose and its composition plays an essential role in modifying the mechanical properties which affects significantly the shielding properties. This study summarizes the results of investigation carried out on concrete containing lime kiln dust, LKD in varying proportions. The objective of this research was to investigate the effects LKD has on the mechanical and shielding properties of concrete using it as part replacement material for cement. Compressive strength, flexural tensile strength, modulus of elasticity, unit mass and density were the mechanical properties investigated whilst linear and mass attenuation coefficients, half and tenth value layers and mean free path investigated for the shielding properties. The ability of concrete to attenuate x-ray intensity is assessed using its mass attenuation coefficient. The average mass attenuation coefficient for 100% concrete at 80 kVp was (0.1529 ± 0.0226) cm2g-1. At the same energy, 90% cement, 10% LKD concrete which had the highest density of (2.4622 ± 0.0218E-3) gcm-3 recorded an average mass attenuation coefficient of (0.1454 ± 0.2157) cm2g-1. The average density for all the concrete types was (2.4093 ± 0.4089E-3) gcm-3. It was observed that increasing LKD ratio affected mechanical and shielding properties of concrete hence for x-ray facilities such as in hospitals and laboratories, LKD can be included in the cement mix used for plastering to form a multilayer aiding in attenuation.
Thesis (MPhil)
Keywords: X - Ray Shielding; Concrete; Lime Kiln Dust